REPRODUCTION OF THE LABOR FORCE AS A FACTOR OF PROVIDING EMPLOYMENT OF YOUTH (Scientific electronic journal "Labor Economics and Human Capital", 2024)
Taking into account that young people make up the bulk of the labor, ensuring their employment is one of the most important aspects of economic development, it is desirable to further improve the system of training and retraining.
Keywords: youth labor market, employment of youth, strategy of a professional training.